DENTAL PRACTICE ADAPTATIONS DURING THE COVID-19 PANDEMIC - Andronic Andrei; Ioana Bianca Todor; Dinu Ștefania; Mariana Păcurar; Sorana Maria Bucur; Victoria Bîrluțiu (Romanian Journal of Oral Rehabilitation)
Aim of the study: this study investigates the impact of the SARS-CoV-2 pandemic on dental practice through a questionnaire developed by four dentists at Lucian Blaga University. Material and method: the questionnaire, refined based on expert feedback, consisted of 14 questions divided into two sections: demographic data (6 questions) and dental practice during the pandemic (8). The second section addressed protocols, protective measures, activity suspension effects, infection rates, and vaccination compliance. Results: distributed to 600 licensed dentists in Sibiu County, the final analysis included 165 complete responses, resulting in a 27.5% response rate. The demographic breakdown revealed 64.2% female and 35.8% male respondents, with the largest age group (47.3%) being 31-40 years. Most participants (68.3%) were general dentists, and 58.8% had over ten years of experience. Only 13.3% of dental practices rated the protocol as satisfactory, 37.0% found it acceptable, and 49.1% deemed it unsatisfactory. The perceived effectiveness of protective measures highlighted that increased personal protective equipment was crucial (mean=3.95). The pandemic negatively affected the profession, with physical discomfort (mean=4.08) and increased stress (mean=3.77) being significant concerns. Statistical analyses utilized ANOVA and Chi-Square tests, revealing statistically significant differences in protocol perceptions (p < 0.05). Conclusion: This study emphasizes the need for improved protocols and supports ongoing adaptations in dental practice during health crises.